(untitled) (American Journal of Islam and Society, 2014)
Despite the progress made in the study of Shi‘i Islam, few publications provide a comprehensive account of its history. Referring primarily to secondary sources, A History of Shi‘i Islam overviews key events going back to the time of Prophet Muhammad to “clarify misunderstandings” and illustrate the various Shi‘i schools’ contribution to Islamic history. From an Ismaili Perspective could have been a helpful subtitle, as will be explained below. The book consists of six chapters: “Introduction: Progress in the Study of Shi‘i Islam,” “The Origins and Early History of Shi‘i Islam,” “The Ithna‘asharis or Twelvers,” “The Ismailis,” “The Zaydis,” and “The Nusayris or ‘Alawis,” respectively. A glossary is provided; however, not all of the terms used by the author are listed. Each chapter is divided into several subsections ...